Annual review of working conditions in the EU: 2003-2004 - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2007)
This first EU-level annual review for the European Working Conditions Observatory (EWCO) summarises the main developments at EU level in the area of working conditions and quality of work and employment. The Foundation paper Quality of work and employment in Europe: Issues and challenges , identifies four dimensions in promoting quality of work: • ensuring career and employment security; • maintaining and promoting the health and well-being of workers; • developing skills and competences; • reconciling working and non-working life. The European strategy for full employment and better jobs for all, as outlined in the Employment Guidelines 2003 (pdf file) , gives a definition of quality in work and employment: 'Quality is a multi-dimensional concept addressing both job characteristics and the wider labour market. It encompasses intrinsic quality at work, skills, lifelong learning and career development, gender equality, health and safety at work, flexibility and security, inclusion and access to the labour market, work organisation and work-life balance, social dialogue and worker involvement, diversity and non-discrimination, and overall work performance.'
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Labor supply -- European Union countries; Electronic books